The influence of virtual laboratories on students’ interest in STEM fields: a longitudinal study in secondary education - Karimova, Batesh; Zhumabekova, Bibigul; Hamzina, Sholpan (Institute of Advanced Engineering and Science, 2025)
The objective of this article is to investigate the impact of virtual laboratories (biology, chemistry, physics, and mathematics) on students’ interest in science, technology, engineering, and mathematics (STEM) fields over six months of study. The study involved 317 participants from Alkey Margulan Pavlodar Pedagogical University (Pavlodar Region, Kazakhstan), who were divided into experimental and control groups. An experimental approach was employed, wherein participants underwent training using virtual laboratories for six months. Statistical methods, specifically t-tests for paired and independent samples, were employed to analyze the results. The experiment revealed a statistically significant positive influence of virtual laboratories on students’ interest in STEM fields. Participants in the experimental group exhibited an increased interest in biology, chemistry, physics, and mathematics compared to the control group. The research findings hold important practical implications for enhancing STEM education. The implementation of virtual laboratories may contribute to an increase in students’ interest in studying STEM disciplines, which is crucial for shaping the future generation of specialists in these fields. Future considerations should involve exploring various types of virtual laboratories, taking into account sociocultural context, and addressing individual differences among students. Additionally, it is essential to investigate the longer-term effects of using digital technologies in STEM education.